2022
DOI: 10.1093/biomet/asac054
|View full text |Cite
|
Sign up to set email alerts
|

Propensity scores in the design of observational studies for causal effects

Abstract: Summary The design of any study, whether experimental or observational, that is intended to estimate the causal effects of a treatment condition relative to a control condition, refers to those activities that precede any examination of outcome variables. As defined in our 1983 article (Rosenbaum & Rubin, 1983), the propensity score is the unit-level conditional probability of assignment to treatment versus control given the observed covariates; so, the propensity score explicitly does not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
0
7
0
4
Order By: Relevance
“…Secondly, upon considering the influence of research characteristics following propensity score matching, it was found that propensity score matching completely eradicated the influence of research characteristics. (Rosenbaum & Rubin, 2023). Thirdly, before conducting propensity score matching, a comparison of learning management models developed for students' analytical thinking revealed that the mean effect size of the studies did not differ significantly from zero (Qa = 4.577), and the residuals from the estimation were not zero (Qb = 1184.007***).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, upon considering the influence of research characteristics following propensity score matching, it was found that propensity score matching completely eradicated the influence of research characteristics. (Rosenbaum & Rubin, 2023). Thirdly, before conducting propensity score matching, a comparison of learning management models developed for students' analytical thinking revealed that the mean effect size of the studies did not differ significantly from zero (Qa = 4.577), and the residuals from the estimation were not zero (Qb = 1184.007***).…”
Section: Discussionmentioning
confidence: 99%
“…Propensity score matching is a statistical method that simulates a randomized controlled trial to reduce bias in nonrandomized samples (Kane et al, 2020;Morgan, 2018). It aims to decrease the variability of confounding variables (Rosenbaum & Rubin, 2023) by ensuring that the comparison groups are as similar as possible (Benedetto et al, 2018). The technique adjusts experimental outcomes based on research characteristics serving as confounding variables, allowing for a controlled comparison of treatment effects (Haukoos & Lewis, 2015;Thoemmes, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The role of PSM is to determine the efficacy of applied treatment and helps in removing selection and endogeneity biases. PSM is an extensively used method to estimate causal effects by matching treatment with control cases based on a set of covariates (Rosenbaum and Rubin 2022). Using PSM, researchers want to compare the outcomes between a treatment and control group by ensuring that both groups have similar characteristics on the observables.…”
Section: Analyses and Findings Study 1 -Evaluating The Impact Of Inte...mentioning
confidence: 99%
“…In parallel with results about propensity scores for observed covariates, we may always represent the combined influence of many unobserved covariates on treatment Zij$Z_{ij}$ by a single scalar unobserved covariate uij$u_{ij}$ with 0uij1$0\le u_{ij}\le 1$ called the “principal unobserved covariate,” the only unobserved covariate that introduces relevant bias into treatment assignment having controlled for boldxij$\mathbf {x}_{ij}$; see Rosenbaum and Rubin (2023, Section 4.2). This principal unobserved covariate is uij=prefixPr(Zij=1|rTij,rCij,boldxij)$u_{ij}=\Pr (Z_{ij}=1\,|\,r_{Tij},\,r_{Cij},\,\mathbf {x}_{ij})$, and it is unobserved because false(rTij,0.16emrCijfalse)$(r_{Tij},\,r_{Cij})$ are never jointly observed.…”
Section: Notation: Potential Outcomes; Two Control Groupsmentioning
confidence: 99%